Effectiveness of smoking cessation on the high-risk population of lung cancer with early screening: a systematic review and meta-analysis of randomized controlled trials until January 2022 - Simin Huang; Oufeng Tang; Xutong Zheng; Hui Li; Yuxin Wu; Liu Yang (BMC, 2023)
Abstract Background Lung cancer has always been the malignant tumor with the highest incidence rate. Smoking is the most important risk factor for lung cancer. Although potential positive effects of smoking cessation interventions on the high-risk population of lung cancer have been observed, evidence of its definitive effect remains uncertain. This study aimed to summarize the evidence related to the effects and safety of smoking cessation interventions for the high-risk population of lung cancer. Methods A systematic literature search was conducted through the following seven databases: PubMed, Embase, Web of Science, CENTRAL, CINAHL, PsycINFO, and Science Direct. Screening and assessment for risk of bias were conducted by two independent reviewers. Meta-analysis was performed for the 7-day-point prevalence of smoking abstinence and continuous smoking abstinence using RevMan 5.3 software. Results Meta-analysis results show that in the 7-day-point prevalence of smoking abstinence (by patient-reported outcome): individualized intervention was significantly higher than that of the standard care [RR = 1.46, 95%CI = (1.04,2.06), P < 0.05]. Moreover, the smoking cessation interventions were significantly elevated than that of standard care [RR = 1.58, 95%CI = (1.12, 2.23), P < 0.05] within 1-6 month follow-up time. In line with the findings in cigarette smoking, the continuous smoking abstinence of E-cigarettes (biochemical verified): E-cigarettes were significantly higher than that of the standard care [RR = 1.51, 95%CI = (1.03, 2.21), P < 0.05], and within 1-6 month follow-up time, the smoking cessation interventions were significantly greater than that of standard care [RR = 1.51, 95%CI = (1.03, 2.21), P < 0.05]. Publication bias was detected possibly. Conclusions The results of this systematic review show that smoking cessation intervention is effective for long-term lung cancer high-risk smokers who participate in early screening, of which E-cigarettes are the best, followed by individual smoking cessation. Trial registration A review protocol was developed and registered in the International Prospective Register of Systematic Reviews (PROSPERO). Trial registration: CRD42019147151. Registered 23 June 2022.